PERSEMBAHAN IBADAH YANG SEJATI DALAM ROMA 12:1 SEBAGAI PROSES PEMBELAJARAN LIFESTYLE UMAT KRISTEN - Heni Perianti Mendrofa (Sekolah Tinggi Teologi Excelsius, 2022)
Abstract: All humans want to enjoy the pleasure and satisfaction of life. This situation is inseparable from the lifestyle of Christians, even though they do it in different ways. This study aims to examine the meaning of true worship, the meaning of true worship in Romans 12:1, and how to offer true worship in Romans 12:1 as a Christian lifestyle learning process. This study uses a literature approach with the results: (1) True worship is an encounter with God fundamentally from the heart directed to the Lord Jesus (2) The offering in Romans 12: 1: (a) the offering of your living body is the total surrender of your whole soul and soul. Enter into the life of God. (b) the offering of your holy bodies is a human act in the likeness of God, who is most holy. (3) Christians always process themselves in learning to train themselves to form a true lifestyle of worship: (a) The process of learning lifestyle as a living offering by doing a total surrender to God. (b) The process of learning lifestyle as an offering of the body (physically as a whole) which is Holy must be carried out throughout life by uniting in one action between the spirit, soul, and body to enter into God's holy life. (c) The lifestyle learning process as an offering pleasing to God must be carried out throughout life, continuously knowing, understanding, studying, and practicing Bible values in daily life.Keywords: true worship offerings; Romans 12:1; learning process; lifestyleAbstrak: Semua manusia ingin menikmati kesenangan dan kepuasan hidupnya. Keadaan tersebut tak luput dari lifestyle umat Kristen meski mereka melakukan dengan cara yang berbeda-beda. Studi ini bertujuan untuk mengkaji pengertian ibadah yang sejati, makna ibadah sejati dalam Roma 12: 1, dan bagaimana persembahan ibadah yang sejati dalam Roma 12:1 sebagai proses pembelajaran lifestyle umat Kristen. Studi ini menggunakan pendekatan pustaka dengan hasil: (1) Ibadah yang sejati adalah perjumpaan dengan Tuhan secara mendasar dari hati yang tertuju kepada Tuhan Yesus (2) Persembahan dalam Roma 12: 1: (a) persembahan tubuhmu yang hidup adalah menyerahan total seluruh jiwa dan raga masuk dalam kehidupan Allah. (b) persembahan tubuhmu yang kudus adalah tindakan manusia serupa dengan Allah, yang Maha kudus. (3) Umat Kristen selalu memproses dirinya dalam pembelajaran melatih diri untuk membetuk lifestyle ibadah yang sejati: (a) Proses pembelajaran lifestyle sebagai persembahan yang hidup dengan cara melakukan penyerahan diri secara total kepada Allah. (b) Proses pembelajaran lifestyle sebagai persembahan tubuhnya (fisik secara menyeluruh) yang Kudus wajib dilakukan sepanjang hidup dengan cara mempersatukan dalam satu tindakan antara roh, jiwa, dan tubuhnya untuk masuk ke dalam kehidupan kudus Allah. (c) Proses pembelajaran lifestyle sebagai persembahan yang berkenan Tuhan wajib dilakukan sepanjang hayat secara terus-menerus mengenal, memahami, mempelajari, dan mempraktikan nilai-nilai Alkitab dalam kehidupan sehari-hari.